2014
DOI: 10.1159/000358921
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Parkinson's Disease in Patients with End-Stage Renal Disease: A Retrospective Cohort Study

Abstract: Background: Studies on dyskinesia and Parkinson's syndrome associated with chronic kidney disease or end-stage renal disease (ESRD) have been mainly limited to case reports or case series studies. This population-based study investigated the risk of Parkinson's disease in patients with ESRD. Methods: From a universal insurance claims database of Taiwan, we established a cohort of 8,325 adults with newly diagnosed ESRD from 1997 to 2010 without a history of Parkinson's disease. A control cohort of 33,382 insure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 31 publications
2
33
2
1
Order By: Relevance
“…A 3‐year follow‐up study based on the Longitudinal Health Insurance Database in Taiwan reported that after adjusting for DM, uremic patients are associated with a 1.81‐fold higher risk of developing parkinsonism than are nonuremic patients . In addition, a 2.56‐year follow‐up cohort study from the same database reported that ESRD was associated with an increased risk of PD, with an adjusted HR of 1.73 (95% CI, 1.39–2.15) . Consistent with these previous study results, our findings provide additional evidence that elderly uremic patients are more vulnerable to the development of PD than are nonuremic individuals, using a population‐based larger sample and with a longer duration of follow‐up.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…A 3‐year follow‐up study based on the Longitudinal Health Insurance Database in Taiwan reported that after adjusting for DM, uremic patients are associated with a 1.81‐fold higher risk of developing parkinsonism than are nonuremic patients . In addition, a 2.56‐year follow‐up cohort study from the same database reported that ESRD was associated with an increased risk of PD, with an adjusted HR of 1.73 (95% CI, 1.39–2.15) . Consistent with these previous study results, our findings provide additional evidence that elderly uremic patients are more vulnerable to the development of PD than are nonuremic individuals, using a population‐based larger sample and with a longer duration of follow‐up.…”
Section: Discussionsupporting
confidence: 90%
“…Although CKD and proteinuria are well known to be related to cardiovascular risk, they have been indicated to also be associated with noncardiovascular complications, cognitive dysfunction, and poor physical functioning in older adults . In addition, 2 recent cohort studies in Taiwan reported an association between chronic uremia and parkinsonism . One study showed that uremic patients had an increased risk of the occurrence of parkinsonism compared with nonuremic patients .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Sociodemographic data including age, sex, and insurance type, and medical data including the presence of comorbid diseases and concurrent medications known to cause parkinsonism were collected [14][15][16][17][18]. Comorbid diseases included diabetes mellitus (ICD-10 codes E10-E14), stroke (ICD-10 codes I60-I66), endstage renal disease (ICD-10 code N18.5), and Alzheimer's disease (ICD-10 code G30).…”
Section: Study Population and Data Collectionmentioning
confidence: 99%